A Process for Developing and Revising a Learning Progression on Sea Level Rise Using Learners' Explanations - McDonald, Robert Christopher (2016)
The purpose of this study was to explore the process of developing a learning progression (LP) on constructing explanations about sea level rise. I used a learning progressions theoretical framework informed by the situated cognition learning theory. During this exploration, I explicitly described my decision-making process as I developed and revised a hypothetical learning progression. Correspondingly, my research question was: What is a process by which a hypothetical learning progression on sea level rise is developed into an empirical learning progression using learners’ explanations? To answer this question, I used a qualitative descriptive single case study with multiple embedded cases (Yin, 2014) that employed analytic induction (Denzin, 1970) to analyze data collected on middle school learners (grades 6-8). Data sources included written artifacts, classroom observations, and semi-structured interviews. Additionally, I kept a researcher journal to track my thinking about the learning progression throughout the research study. Using analytic induction to analyze collected data, I developed eight analytic concepts: participant explanation structures varied widely, global warming and ice melt cause sea level rise, participants held alternative conceptions about sea level rise, participants learned about thermal expansion as a fundamental aspect of sea level rise, participants learned to incorporate authentic scientific data, participants’ mental models of the ocean varied widely, sea ice melt contributes to sea level rise, and participants held vague and alternative conceptions about how pollution impacts the ocean. I started with a hypothetical learning progression, gathered empirical data via various sources (especially semi-structured interviews), revised the hypothetical learning progression in response to those data, and ended with an empirical learning progression comprising six levels of learner thinking. As a result of developing an empirically based LP, I was able to compare two learning ...